Effect of harmonics on reduction of unbalance in three-phase four wire composite network - Ravichandran Durgayandi; Muruganantham Narayanan (Institute of Advanced Engineering and Science, 2023)
The unbalanced current drawn by the composite loads in small-scale industries is mainly due to single-phase loads. Any operation of single-phase loads will cause unbalance of current and produce distortion due to non-linear loads. The neutral current is increased and voltage at the load end is reduced due to an increase in unbalanced linear loads. Industries find it difficult to balance the load and control the neutral current. To overcome the problem, this work aims to add a passive network in different configurations along with shunt active power filter. A set of linear and non-linear loads are considered in the network and the results are discussed in this paper. The L and C values are designed to compensate for the required reactive power and the canceling of negative and zero sequence current quantities due to unbalance in the circuit. This paper also reviewed the effect of active filter RMS current at an unbalanced load current.